Intraductal Ultrasonography in Pancreatobiliary Diseases - Bansal, Rinkesh Kumar; Choudhary, Narendra S.; Puri, Rajesh; Sharma, Zubin; Patle, Saurabh; Patil, Gaurav Kumar (Journal of Digestive Endoscopy, 2017)
Intraductal ultrasonography (IDUS) utilizes probe catheter and operates at a higher frequency (12–30 MHz). It can be passed down the biopsy channel of a side‑view endoscope during endoscopic retrograde cholangiopancreatography, and it provides real‑time, high‑quality imaging of pancreatobiliary ducts and the surrounding structures. IDUS has been used in defining choledocholithiasis, evaluating biliary as well as pancreatic strictures or thickening, and local staging of tumor. We shall discuss the utility of IDUS in the current review.
Keywords: Biliary stricture; endoscopic ultrasound; intraductal ultrasound; pancreatobiliary diseases